Screening of Fungi for Decolorization of Wastewater from Pulp and Paper Industry - Waraporn Apiwatanapiwat,; Prisnar Siriacha,; Pilanee Vaithanomsat, (Agriculture and Natural Resources, 2006)
Sixty-four fungal strains collected from decomposed woods in Khao-Yai National Park were evaluated for their ability to decolorize the wastewater from pulp and paper industry. Among the strains collected, KAPI03, KAPI04, KAPI13, KAPI25, KAPI30, KAPI39 and KAPI50 were able to grow well on agar containing synthetic lignin indicating that they could utilize synthetic lignin as nutrient for their growth. However, when they were tested for their effectiveness on decolorization of the wastewater from pulp and paper mill, it was indicated that strains KAPI25, KAPI39 and KAPI50 were the most efficient strains able to decolorize the pulping wastewater by 54.4, 54.9 and 53.7%, respectively. These strains were identified by basic morphology as the Genus Trichaptum (KAPI25), Datronia (KAPI39) and Trametes (KAPI50).